2022
DOI: 10.3390/jcm11061628
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Postpartum Depression in Romanian Women during Two Periods of COVID-19 Pandemic

Abstract: Postpartum depression is a major mental health disorder that can negatively affect both mother and baby. In addition, the COVID-19 pandemic associated with extreme measures of the lockdown had profound effects on humanity, increasing the rates of anxiety and depression, especially among women in the postpartum period. The aim of this study was threefold: to determine the prevalence of postpartum depression, to compare the prevalence of postpartum depression at two different times during the COVID-19 pandemic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…This study found no significance for characteristics such as age, educational level, number of children, chronic illness, monthly income, having a work, having prenatal complications, or gestational age at the time of delivery. Similarly, Citu et al found no significance for characteristics such as age, education level, place of residence and type of birth, number of children, and sex of the infant, or pregnancy complications [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found no significance for characteristics such as age, educational level, number of children, chronic illness, monthly income, having a work, having prenatal complications, or gestational age at the time of delivery. Similarly, Citu et al found no significance for characteristics such as age, education level, place of residence and type of birth, number of children, and sex of the infant, or pregnancy complications [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…If an infant is infected, he or she may have a fever and a sore throat, especially since most infants under the age of 1 can only express pain by crying, which adds to the psychological burden on the mothers ( 55 ). At present, there have been studies that have found COVID-19 can trigger or exacerbate postnatal depression ( 56 , 57 ). However, most Chinese citizens are unaware of postnatal depression and do not usually seek psychological help in advance.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous research demonstrating higher prevalences of postpartum depression during pandemic phases with higher numbers of infections. For example, Citu et al [18] found that those women who gave birth during the fourth pandemic wave had a higher rate of depression than those from the first wave, being characterized by a difference of more than 17%. Similarly, Babicki et al [19] studied postpartum mental health during the first, second, and third waves, and found that anxiety and depressive symptoms increased as the pandemic progressed.…”
Section: Discussionmentioning
confidence: 99%